Electrical Safety in the farm: Case Study Research at Michigan USA 2010 - Fathurrahman, Fathurrahman (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
Electrical safety concern has been rise from early utilization of electricity. This report is about electrical accident that took place in one agricultural farm in Michigan, USA in summer 2010. A bilingual Latino farm worker (28) was electrocuted in a 6000-acre potato farm when he touched one of tower of self-propelled central pivot irrigators, which is irrigating the farm at that time. The delta corner-grounded system is used at the farm. The multicultural environment is also escalated the risk.